RESERVOIR DISTRIBUTION ANALYSIS AND NET PAY INTERVAL OF 920 - 990 SANDSTONE IN SEKELOA FIELD, KUTAI BASIN USING STOCHASTIC SEISMIC INVERSION AND SEISMIC ATTRIBUTE METHODS - Suara Ning Tyas, Tania
The Kutai Basin in East Kalimantan is one of the largest and deepest basins in Indonesia with hydrocarbon potential. Reservoirs in the Kutai Basin are in the Miocene-aged Balikpapan and Kampung Baru formations and consist of thin layers that are difficult to identify. Therefore, conventional interpretation methods are difficult to use, causing uncertainty in reservoir characterization that can increase exploration and production risks. This study aims to map the distribution of sand reservoirs and the distribution of net pay in the 920 - 990 sandstone sequence in Sekeloa Field, Kutai Basin. In order to achieve this goal, the stochastic inversion method is used as a more effective approach because it is able to overcome the challenges of thin layer interpretation better than other inversion methods. The stochastic inversion method is a seismic inversion technique that uses a probabilistic approach and random simulation to model the uncertainty in seismic data. Based on log data analysis, sand and shale lithologies can be separated by the elastic parameter P-Impedance. While net pay and wet sand/shale can be separated by elastic parameters P-Impedance and Vp/Vs. Then the sand and net pay distribution map is made from the slicing of stochastic inversion results and RMS Amplitude attributes used as validation. In the RMS Amplitude map of sandstone target 920 there is a high amplitude anomaly indicated as a channel in the eastern part of Sekeloa Field, where the pattern is also seen in the P-Impedance and Vp/Vs maps with low values. In addition, the RMS Amplitude maps of sandstone targets 930, 960 and 990 have high amplitude anomalies indicated as slope fans and channels in the eastern part of Sekeloa Field, where the pattern is also seen in the P-Impedance and Vp/Vs maps with low values. The P-Impedance and Vp/Vs maps from the stochastic inversion show a more detailed sandstone pattern that is not present in the RMS Amplitude map. This is because stochastic inversion is not influenced by bandlimited seismic data like the RMS Amplitude results.